Profession vs Ethics - Hossein Sadri (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
This article studies the process of professionalization in general and particularly in architecture and reviews the concept of professional ethics and the codes and documents related to it. The article investigates on the motivations of the conflicts between the documents of professional ethics with the ethical values by criticizing several codes of professional conducts produces by the main professional organizations in the field of architecture. The article proposes an ethical approach which can go beyond and above professions and their limited professional interests to be able to prevent the unethical professional conducts.